2016
DOI: 10.1111/1365-2656.12580
|View full text |Cite
|
Sign up to set email alerts
|

Carry‐over effects on the annual cycle of a migratory seabird: an experimental study

Abstract: Summary Long‐lived migratory animals must balance the cost of current reproduction with their own condition ahead of a challenging migration and future reproduction. In these species, carry‐over effects, which occur when events in one season affect the outcome of the subsequent season, may be particularly exacerbated. However, how carry‐over effects influence future breeding outcomes and whether (and how) they also affect behaviour during migration and wintering is unclear.Here we investigate carry‐over effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 55 publications
3
51
0
Order By: Relevance
“…, Fayet et al. ). Alternatively, this could be a result of flight impairment due to an advance in their molt schedule (Cherel et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, Fayet et al. ). Alternatively, this could be a result of flight impairment due to an advance in their molt schedule (Cherel et al.…”
Section: Discussionmentioning
confidence: 99%
“…, Fayet et al. ). Theoretically, life history theory predicts that short‐lived species, with lower chances to survive until the next breeding attempt than long‐lived species, should invest as much as possible in current reproductive events, even when this effort may compromise their survival for future breeding attempts (Lindén and Moller , Stearns ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that birds having a higher foraging activity during winter were more likely to fail to reproduce during the subsequent breeding season (Daunt et al., ; Kazama et al., ; Shoji et al., ). Individuals seemed therefore to adapt their winter foraging effort as a constrained response to their own body condition rather than as an active decision concerning future breeding (Fayet et al., ; Shoji et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…A major advantage of biologging is the potential to estimate food supply over multiple spatial and temporal scales. Year-round biologger deployments (e.g., Daunt et al, 2014;Fayet et al, 2016) can document year-round variation in food supply over large scales. Repeated biologger deployments on the same individuals over multiple years (e.g., Daunt et al, 2014) will allow us to examine inter-and intra-individual responses to variation in food supply.…”
Section: Phalacrocorax Bougainvilliorummentioning
confidence: 99%